A New Species of Eriosema (Leguminosae, Papilionoideae, Phaseoleae) from Minas Gerais, Brazil - Cândido, Elisa Silva; Fortuna-Perez, Ana Paula; Bezerra, Luísa M.p.a.; Aranha Filho, João Luiz Mazza (Phytotaxa, 2014)
Eriosema tozziae, a new species of Leguminosae (Papilionoideae, Phaseoleae, Cajaninae) from Minas Gerais is described and illustrated. Similar to E. defoliatum, it differs morphologically from the latter by the persistent leaves in the reproductive phase (vs. caducous in E. defoliatum) and the shorter inflorescences (10–13 cm long vs. 15–30 cm long in E. defoliatum). An identification key for the Eriosema species in Minas Gerais is also provided.